1995
DOI: 10.1136/mp.48.1.m12
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemically detectable p53 and mdm-2 oncoprotein expression in colorectal carcinoma: prognostic significance

Abstract: Aims-To investigate the correlation between the expression of the p53 and mdm-2 oncoproteins and to assess their prognostic value in colorectal cancer.Methods-Using a polyclonal (CM1) and a monoclonal antibody directed against p53 and mdm-2, respectively, these oncoproteins were stained immunohistochemically in 109 colorectal adenocarcinomas.Results-p53 was detected in less than 10% of tumour cells in 11 of 109 adenocarcinomas, in 10-50% of tumour cells, in 17 of 109 adenocarcinomas, and in more than 50% of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

1997
1997
2003
2003

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
2
13
0
2
Order By: Relevance
“…The same authors also showed that both nuclear and p53 protein expression appeared to be important in a multivariate analysis (Sun et al, 1993). A further study (Ofner et al, 1995) showed that there was no relationship between p53 protein expression and grade or stage parameters, such as Dukes' stage, in colorectal cancer. This finding has been reiterated (Mulder et al, 1995) in a study of 109 colorectal cancers.…”
Section: Discussionmentioning
confidence: 92%
“…The same authors also showed that both nuclear and p53 protein expression appeared to be important in a multivariate analysis (Sun et al, 1993). A further study (Ofner et al, 1995) showed that there was no relationship between p53 protein expression and grade or stage parameters, such as Dukes' stage, in colorectal cancer. This finding has been reiterated (Mulder et al, 1995) in a study of 109 colorectal cancers.…”
Section: Discussionmentioning
confidence: 92%
“…In immunohistochemical studies using monoclonal anti-MDM2 protein antibody, the incidence of MDM2 immunohistochemical (over)expression in human cancers has been reported to be 30% in bladder cancers (Lianes et al, 1994), 20% in colorectal cancers (Ofner et al, 1995), 3% in ovarian cancers (Foulkes et al, 1995), 40% in oral carcinoma (Matsumura et al, 1996) and 22-41% in breast cancers (Marchetti et al, 1995b;McCann et al, 1995). In NSCLC, whereas Marchetti et al (1995a) reported that MDM2 oncogene product expression was detected immunohistochemically only in three (6%) patients with gene amplification, it was detected in the present study in 24% of patients, independently of MDM2 gene amplification status.…”
Section: Post-operative Prognosismentioning
confidence: 99%
“…Incubation with the primary antibodies (monoclonal MDM2 antibody, IF-2, Oncogene Science, USA, and monoclonal p53 antibody, DO-7, Novocastra Laboratories, UK), British Journal of Cancer (1997) 75(9), [1302][1303][1304][1305][1306][1307][1308] . Cancer Research Campaign 1997 the enzyme colour reaction, haematoxylin counterstaining and mounting were carried out as described elsewhere (Foulkes et al, 1995;Marchetti et al, 1995a and b;McCann et al, 1995;Ofner et al, 1995;Matsumura et al, 1996). Immunostaining results were assessed, taking into account the cancer cells whose nuclei showed positive immunoreactivity for MDM2 ( Figure 1) or p53 protein.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by MildeLangosch et al, (1995) on vulvar cancer, loss of p53 function was associated with a high risk of progression and an unfavourable prognosis. In the literature the prognostic value of p53 seems to be controversial, because in some studies p53 is considered prognostic relevant (Charpin et al, 1995;Esrig et al, 1994;Florenes et al, 1994;Shurbaji et al, 1995;Sun et al, 1992;Vogt et al, 1997), whereas in other studies it is not King et al, 1996;Ofner et al, 1995;Xerri et al, 1994;Younes et al, 1995). It may be that the prognostic value of p53 depends on whether mutation of p53 occurs during carcinogenesis, progression or metastasis of the tumour.…”
Section: Discussionmentioning
confidence: 95%